2013
DOI: 10.1017/s0029665113002085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carrot feeding to APCMin mouse on intestinal tumours

Abstract: Multiple studies show that diets containing carrot are associated with a reduced risk of a range of cancers such as bladder cancer (1) . Carrots contain several types of bioactive compounds with potentially beneficial effects, including polyacetylenes such as falcarinol, which for example are responsible for the cytotoxic effects of carrot juice on leukaemia cell cultures (2) . Mice with the APC Min mutation develop multiple polyps in both the small and the large intestine by age around three months and have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The research carried out to date has shown that feeding freeze‐dried carrot to APC Min mice (which have a mutation at codon 850 in the Apc gene and so develop intestinal tumours spontaneously) substantially and significantly reduced tumour number and tumour volume (Saleh et al . ). Research is currently ongoing to determine which compounds are involved and if the effect can be extended to humans.…”
Section: Research Highlights From the Human Nutrition Research Centrementioning
confidence: 97%
“…The research carried out to date has shown that feeding freeze‐dried carrot to APC Min mice (which have a mutation at codon 850 in the Apc gene and so develop intestinal tumours spontaneously) substantially and significantly reduced tumour number and tumour volume (Saleh et al . ). Research is currently ongoing to determine which compounds are involved and if the effect can be extended to humans.…”
Section: Research Highlights From the Human Nutrition Research Centrementioning
confidence: 97%
“…More detailed studies were performed using animal models. The consumption of carrot powder reduced the growth of intestinal tumours in an Apc Min/+ mouse colon cancer model [ 115 , 116 ]. A study examined colon preneoplastic lesions in AOM-treated rats that were fed carrots (10% freeze-dried carrot with a natural concentration of FaOH at 35 µg/g), FaOH (purified FaOH mixed at 3.5 µg/g in food) or a control for 18 weeks.…”
Section: Cancermentioning
confidence: 99%
“…Mice with the APC Min mutation are a common model of cancer in the small intestine and colon, to study the role of diet on tumours ( 2 ) . A previous study showed a substantial reduction in number of visible tumours when mice were fed carrot-supplemented diet throughout their lifetime (including in utero) ( 3 ) . The main aim of the study was to investigate if the active substances in carrot would be able to reduce the growth of intestinal tumours in APC Min mice when the carrot treatment was started only after the fifth week (after weaning).…”
mentioning
confidence: 99%